Experience with degarelix in the treatment of prostate cancer. (February 2013) - Shore, Neal D.
Degarelix is a gonadotrophin-releasing hormone (GnRH) antagonist for the first-line treatment of androgen-dependent advanced prostate cancer. It has a direct mechanism of action that blocks the action of GnRH on the pituitary with no initial surge in gonadotrophin or testosterone levels. Degarelix is the most extensively studied and widely available GnRH antagonist worldwide. Clinical studies have demonstrated similar efficacy to the GnRH agonist leuprolide in achieving testosterone suppression in patients with prostate cancer. However, degarelix produces a faster suppression of testosterone and prostate-specific antigen (PSA), with no testosterone surge or microsurges, thus preventing the risk of clinical flare in advanced disease. Clinical trials have demonstrated that degarelix can offer improved disease control when compared with a GnRH agonist in terms of superior PSA progression-free survival (suggesting that degarelix likely delays progression to castration-resistant disease), and a more significant impact on bone serum alkaline phosphatase and follicle-stimulating hormone. Degarelix is generally well tolerated, with no reports of systemic allergic reactions in any clinical studies. In conclusion, degarelix offers clinicians a rational first-line hormonal monotherapy option for the management of advanced prostate cancer.